ProTesters: a board game for teaching the testing process - Moreira, Gabriel Goncalves; Reinehr, Sheila; Malucelli, Andreia; Van Amstel, Frederick (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
Despite being the most used approach in teaching software testing in Brazil, the traditional teaching method might not simulate, facilitate or motivate the learning of the testing process and its activities. As a result, undergraduate students may not understand a basic testing process and its components, nor be motivated to learn about the content. One approach that can facilitate the teaching of the software testing process and promote student motivation is educational games. Although there are several educational games for teaching software testing, no game was found on literature that addresses the entire testing process, with its roles, artifacts and activities. This work presents the development of an educational game to support and motivate the learning of a basic software testing process. The research method was Design Science Research. For the development of the game, several playtestings were carried out to verify if the new proposal was able to motivate and teach the proposed content. To evaluate the fulfillment of the research objectives, an experiment was performed with 16 participants, and it was possible to verify a gain of specific knowledge of the participants after the experience with the game. In addition, positive effects were observed on motivational aspects perceived by the players with the game for the learning of the themes involved.